ANALISIS USAHA TANI KAKAO (Theobroma cacao L.) DI DESA BLORO KECAMATAN NITA KABUPATEN SIKKA - Abraham Colson Wangge Tani, Mariano; Nong, Fiator; Yakob Da Rato, Yoseph (Universitas Cokroaminoto Palopo, 2025)
The Independent Campus Independent Learning Activity Program (MBKM) is held by the Agricultural Extension Center (BPP) in Nita District, Sikka Regency, East Nusa Tenggara Province. It will be carried out for 4 months, starting from September to December 2024. This internship aims to analyze cocoa farming in Bloro village, Nita District, Sikka Regency. The method used to analyze data in this activity is a quantitative analysis method, namely data obtained from research in the form of numbers arranged in tables which will then be discussed and analyzed using a predetermined equation model. The research results show that cocoa farming in Bloro Village, Nita District, Sikka Regency is worth pursuing because the total income is IDR 955,377 and the total costs are IDR 602,396. So you get an average receipt of IDR 1,557,773. Based on the calculation of business feasibility (R/C), namely the ratio of income to total production costs greater than zero, namely a comparison figure of 2.58 > 1, it can be concluded that the farming business can be said to be successful. profitable and worth running.